Remarks on the Kuehn-Hamburger Paper - Shycon, Harvey N.; Maffei, Richard B. (Management Science, 1963)
The general conclusion of our examination of the work of the Messrs. Kuehn and Hamburger [Kuehn, A. A., M. J. Hamburger. 1963. A heuristic program for locating warehouses. Management Sci. 9(4) 643–666.] is that they have made available an important tool for the study of the warehouse location problem. At present it appears to have significant limitations, but it is likely that further work can make it more useful. Ultimately some combination of these methods as a first approximation, and then the use of simulation techniques may provide the answer.